Ficus benghalensis — A comprehensive review on pharmacological research, nanotechnological applications, and patents - Preeti Singh, Jyotika Dhankhar, Rajeev Kumar Kapoor, Dhirendra Kumar, Saurabh Bhatia,,, Ahmed Al-Harrasi, Asha Sharma (Journal of Applied Pharmaceutical Science, 2023)
Plants have been an outstanding source of medicine for an incredibly long time. They are mentioned in Ayurveda, Siddha, and Unani as a fundamental source of bioactive compounds to cure and prevent several human body ailments. This review aims to recapitulate diverse medicinal and cosmetic uses, phytochemical constituents, and pharmacological actions of F. benghalensis (Banyan tree), one of India’s most sacred medicinal trees. Banyan tree extracts have shown antioxidant, antidiabetic, hypolipidemic, anthelmintic, antihyperglycemic, immunomodulatory, antihyperlipidemic, hypocholesterolemic, anti-inflammatory, analgesic, antimicrobial, larvicidal, anti-diarrhoeal, antimutagenic, hepatoprotective, anti-arthritic, antiallergic, and immunostimulatory effects. All plant parts such as leaf, stem bark, aerial root, fruit, bud, and latex are used in the conventional medication system to treat several human diseases. This review also highlights the recent commercial applications of F. benghalensis, especially in the field of nanotechnology. The patent landscape of said plant has been studied and analyzed in detail, confirming its role in medicinal formulations, disease therapy, cosmetics, and agriculture. Overall, the present review provides detailed and comprehensive information on phytochemistry, ethnomedical and therapeutic potential, commercial applications, and patent filings of one of the prominent species of the genus Ficus.